An integrated proteomic and transcriptomic analysis of perivitelline fluid proteins in a freshwater gastropod laying aerial eggs - Mu, Huawei (2017)
Proteins of the egg perivitelline fluid (PVF) that surrounds the embryo are critical for embryonic development in many animals, but little is known about their identities. Using an integrated proteomic and transcriptomic approach, we identified 64 proteins from the PVF of Pomacea maculata, a freshwater snail adopting aerial oviposition. Proteins were classified into eight functional groups: major multifunctional perivitellin subunits, immune response, energy metabolism, protein degradation, oxidation-reduction, signaling and binding, transcription and translation, and others. Comparison of gene expression levels between tissues showed that 22 PVF genes were exclusively expressed in albumen gland, the female organ that secretes PVF. Base substitution analysis of PVF and housekeeping genes between P. maculata and its closely related species Pomacea canaliculata showed that the reproductive proteins had a higher mean evolutionary rate. Predicted 3D structures of selected PVF proteins showed that some nonsynonymous substitutions are located at or near the binding regions that may affect protein function. The proteome and sequence divergence analysis revealed a substantial amount of maternal investment in embryonic nutrition and defense, and higher adaptive selective pressure on PVF protein-coding genes when compared with housekeeping genes, providing insight into the adaptations associated with the unusual reproductive strategy in these mollusks. Significance There has been great interest in studying reproduction-related proteins as such studies may not only answer fundamental questions about speciation and evolution, but also solve practical problems of animal infertility and pest outbreak. Our study has demonstrated the effectiveness of an integrated proteomic and transcriptomic approach in understanding the heavy maternal investment of proteins in the eggs of a non-model snail, and how the reproductive proteins may have evolved during the transition from laying underwater eggs to aerial eggs.